Pengaruh Digital Marketing, Kualitas Pelayanan, dan Promosi Terhadap Kepuasan Konsumen Di Ayam Kremes Purwodadi Kota Purwodadi - Abdurrahman Hamam; Sri Martono (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2024)
Background : Currently the culinary business is a very promising business, because food is a basic need for society. Digital marketing is a system that has been embedded in the world of marketing in the digital era, in this era all forms of information can be received by the public very easily and quickly. A form of consumer assessment of the level of service that has been received by consumers, good service is certainly expected by consumers to provide a sense of satisfaction, called service quality. Apart from that, promotion is also a form of marketing communication in increasing people's purchasing power. So in assessing consumer satisfaction, it is referred to as feelings of pleasure or disappointment that arise as a result of comparing the results of products and services that are in accordance with consumer needs, what is expected by consumers to feel very satisfied.Purpose: Describe and analyze the influence of digital marketing on consumer satisfaction at Ayam Kremes Purwodadi, describe and analyze the influence of service quality on consumer satisfaction at Ayam Kremes Purwodadi, describe and analyze promotions on consumer satisfaction at Ayam Kremes Purwodadi, describe and analyze the influence of digital marketing, service quality and promotion simultaneously on consumer satisfaction at Ayam Kremes Purwodadi.Methods: This research uses a quantitative approach. Determining the sample size used Cooper and Emory theory and obtained a sample of 100 respondents. Analyzed using IBM SPSS Statistics Version 25 Forwindows statistical analysis techniques.Conclusion: digital marketing, service quality and promotion play a role in increasing consumer satisfaction.Suggestion: Further research can be carried out by increasing the number of respondents so that they can represent consumers at Ayam Kremes Purwodadi in terms of testing the influence of consumer satisfaction. Apart from the variables examined in this research, there are still many other variables that can influence consumer satisfaction when making a purchase.